Peran GIBEI dalam Membentuk Budaya Investasi Mahasiswa Universitas Hasyim Asy'ari: Studi Fenomenologi - rifardi, lailatul maghfiroh putri; Haryanti, Peni (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study aims to understand the role of the Indonesian Stock Exchange Investment Gallery (GIBEI) in shaping the investment culture among students at Hasyim Asy'ari University. The presence of GIBEI in universities is expected to increase financial literacy and encourage student interest in the capital market. This study uses a qualitative approach with a phenomenological method to explore students' experiences and perceptions of GIBEI. Data was collected through in-depth interviews with students who actively participated in GIBEI activities and observations of investment learning activities. The results showed that GIBEI had a significant impact on shaping students' understanding of capital market investment, increasing their interest in investing, and changing their mindset from consumptive to more productive and future-oriented. GIBEI also serves as a practical learning forum that bridges academic theory with real investment practice. However, there are still challenges in terms of student participation. This study is expected to contribute to the development of financial literacy programs in higher education and increase the effectiveness of GIBEI as a medium for investment learning.